Morphometric variation in the species of two subfamilies of lycaenid butterflies (Lepidoptera: Lycaenidae) of Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2018)
A laboratory examination was done on the morphometric variation of lycaenid butterflies. Identifying characteristics, viz. forewing length (FWL), hind wing length (HWL), body length (BdL) and antennal length (AntL) were used for the analysis. A total of 514 individuals of lycaenid butterflies was identified under two subfamilies Polyommatinae and Theclinae. Among them 265 individuals were placed under 19 species of Polyommatinae and 249 individuals under 25 species of Theclinae. ANOVA tests were conducted to find differences between the butterfly species of the two subfamilies through identifying characters like FWL (F=10.37, P=0.005), HWL (F=3.81, P=0.067), BdL (F=5.78, P=0.027) and AntL (F=2.77, P=0.114). A linear regression analysis of FWL, HWL, BdL and AntL of the species under the two subfamilies showed significant differences between Polyommatinae and Theclinae. These differences stand among the species of both the subfamilies and produced good results to identify the species more correctly.J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(1): 9-16